A Generalizability Analysis of the Meaning in Life Questionnaire for Chinese Adolescents - Chen, Wei; Gao, Rongfen (Frontiers in Psychology, 2021)
The level of meaning in life not only affects the individual physical health, but also is closely related to the individual mental health. Currently, many self-reported questionnaires are being used to measure the meaning in life of Chinese adolescents. Using the multivariate generalizability theory, this study investigated the psychometric properties and the internal structure of the Meaning in Life Questionnaires, the most widely used questionnaire assessing the level of Chinese adolescents. The data were sample of 1951 junior high school students from Guizhou, China. Multivariate random measurement mode p˙ × i° is the Primary analytic approach. Results showed that the generalizability coefficient and dependability index of the scale were 0.86 and 0.85, respectively. The generalizability coefficients of presence of meaning and search for meaning were 0.76 and 0.85 respectively, and the dependability indexes were 0.75 for MLQ-P and 0.85 for MLQ-S. The design of each factor for MLQ is reasonable in terms of score ratio and the number of projects. In brief, the reliability and factor structure of the scale are satisfactory.